Importance of Taiman in Larval-Pupal Transition in Leptinotarsa decemlineata - Xu, Qing-Yu; Du, Jun-Li; Mu, Li-Li; Guo, Wen-Chao; Li, Guo-Qing (Frontiers in Physiology, 2019)
Insect Taiman (Tai) binds to Methoprene-tolerant to form a heterodimeric complex, mediating juvenile hormone (JH) signaling to regulate larval development and to prevent premature metamorphosis. Tai also acts as a steroid receptor coactivator of 20-hydroxyecdysone (20E) receptor heterodimer, ecdysone receptor (EcR) and Ultraspiracle (USP), to control the differentiation of early germline cells and the migration of specific follicle cells and border cells in ovaries in several insect species. In holometabolous insects, however, whether Tai functions as the coactivator of EcR/USP to transduce 20E message during larval-pupal transition is unknown. In the present paper, we found that the LdTai mRNA levels were positively correlated with circulating JH and 20E titers in Leptinotarsa decemlineata; and ingestion of either JH or 20E stimulated the transcription of LdTai. RNA interference (RNAi)-aided knockdown of LdTai at the fourth (final) instar stage repressed both JH and 20E signals, inhibited larval growth and shortened larval developing period. The knockdown caused 100% larval lethality due to failure of larval-pupal ecdysis. Under the apolysed larval cuticle, the LdTai RNAi prepupae possessed pupal thorax. In contrast, the processes of tracheal ecdysis and fat body remodeling were uncompleted. Neither JH nor 20E rescued the aforementioned defectives in LdTai RNAi larvae. It appears that Tai mediates both JH and 20E signaling. Our results uncover a link between JH and 20E pathways during metamorphosis in L. decemlineata.